DEVELOPMENT AND VALIDATION OF LC-MS/MS METHOD FOR ESTIMATION OF UROCARB IN HUMAN PLASMA - DRAPAK, IRYNA; ZIMENKOVSKY, BORYS; PEREKHODA, LINA; KOVALENKO, SERGIY; LOGOYDA, LILIYA (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study was aimed to develop a rapid, specific and sensitive method based on LC-MS/MS method was developed for the determination of urocarb using etomidate as an internal standard. Methods: Chromatography was achieved on Discovery C18, 50 × 2.1 mm, 5 μm column. Samples were chromatographed in a gradient mode (eluent A (acetonitrile-water–formic acid, 5: 95: 0.1 v/v), eluent B (acetonitrile–formic acid, 100: 0.1 v/v)). The initial content of the eluent B of 8%, which increases linearly to 1.0 min to 100%, is maintained up to 1.5 min and returned to the original 8% to 1.51 min. The mobile phase was delivered at a flow rate of 0.400 ml/min into the mass spectrometer ESI chamber. The sample volume was 4 μl. Results: The total chromatographic run time was 2.0 min and the elution of urocarb and IS (etomidate) occurred at 1.53 and 1.67 min, respectively. A linear response function was established at 1-100 ng/ml for urocarb and etomidate in human plasma. The % mean recovery for urocarb in LQC, MQC and HQC was 104.1 %, 100.0 % and 97.4 %. The lowest concentration with the RSD<20% was taken as LLOQ and was found to be 1.03 ng/ml for urocarb. The within-run coefficients of variation ranged between 0.271 % and 0.478 % for urocarb. The within-run percentages of nominal concentrations ranged between 99.12 % and 100.21 % for urocarb. The between-run coefficients of variation ranged between 0.388 % and 0.601 % for urocarb. The between-run percentages of nominal concentrations ranged between 98.78 % and 101.11 % for urocarb. Conclusion: A highly sensitive, specific, reproducible, rapid and high-throughput LC-MS/MS assay was developed and validated to quantify urocarb in human plasma as per the regulatory guidelines. Due to the sensitivity of the developed method, it can be applied to the monitoring of plasma levels in the analysis of drug in preclinical and clinical pharmacokinetic studies. All the parameters and results were found within the acceptance limit as given in the validation protocol.